Ansari, Zafar Ishaq. “The Scientific Exegesis (Tafsīr) of the Qur’an,” Year 9, Issue 35 (Winter 1425 AH/ 2004 CE), Pp. 43-64. - أنصاري ظفر إسحق (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2004)
Zafar Ishaq Ansari’s study is a sequel to earlier studies that focused on the scientific exegesis of the Qur’an. It aims to shed light on this trend of studies over the past quarter century. The article treats the subject matter within the following themes: is the Qur'an a book of guidance or a book of knowledge/science?; the correlation between the underdevelopment of Muslims and neglect of verses addressing cosmological phenomena in the Qur'an; efforts to reveal concordance between natural sciences and cosmological verses in the Qur'an; and the dangers of emphasizing the concordance of contemporary sciences of the current era with the Qur'an.